Prefrontal hypoactivation during cognitive control in early abstinent methamphetamine-dependent subjects - Nestor, Liam J.; Ghahremani, Dara G.; Monterosso, John; London, Edythe D. (Psychiatry research. Neuroimaging, 2011)
Individuals who abuse methamphetamine (MA) perform at levels below those of healthy controls on tests that require cognitive control. As cognitive control deficits may influence the success of treatment for addiction, we sought to help clarify the neural correlates of this deficit. MA-dependent (n=10, abstinent 4–7days) and control subjects (n=18) performed a color-word Stroop task, which requires cognitive control, during functional MRI (fMRI). The task included a condition in which participants were required to respond to one stimulus dimension while ignoring another conflicting dimension, and another condition without conflict. We compared the groups on performance and neural activation in the two conditions. MA-dependent subjects made more errors and responded more slowly than controls. Controlling for response times in the incongruent condition, voxel-wise mixed effects analyses (whole-brain corrected) demonstrated that MA-dependent subjects had less activation than control subjects in the right inferior frontal gyrus, supplementary motor cortex/anterior cingulate gyrus and the anterior insular cortex during the incongruent condition only. MA-dependent subjects did not exhibit greater activation in any brain region in either of the Stroop conditions. These preliminary findings suggest that hypofunction in cortical areas that are important for executive function underlies cognitive control deficits associated with MA dependence.